Strategic planning and implementation practices at the Kisii county government in Kenya - Opano, Josphat Orangi; Shisia, Adam; Sang, William; Josee, Veronese Marie (My University, 2013)
The aim of this study was to ascertain strategic planning and implementation practices at the Kisii county government in Kenya. The researcher collected qualitative data from the County secretary, Deputy Speaker, County Development Officer (CDO) and county executives. The total number of targeted respondents was 10 and the researcher managed to interview 7 of the respondents. The study was a case study of Kisii County in Kenya. The data was collected through face to face interviews with the respondents. It was revealed that Kisii County has a number of challenges that can be solved through proper strategic planning. The County has a well stated vision and mission that focus on the country’s vision 2030. Stakeholders such as the electorate, the county executive, professional and civic leaders are involved in the strategic planning and implementation process. It is also clear that financial and human resources are the main resources that are required in the implementation of the strategic plan. The main challenge in strategic planning and implementation is financial constraints.
Keywords: Strategic Planning; Implementation Practices; Kisii County; Kenya’s vision 2030